2014
DOI: 10.3945/jn.113.190173
|View full text |Cite
|
Sign up to set email alerts
|

Processed Meat Intake Is Unfavorably and Fish Intake Favorably Associated with Semen Quality Indicators among Men Attending a Fertility Clinic

Abstract: Emerging literature suggests that menÕs diets may affect spermatogenesis as reflected in semen quality indicators, but literature on the relation between meat intake and semen quality is limited. Our objective was to prospectively examine the relation between meat intake and indicators of semen quality. Men in subfertile couples presenting for evaluation at the Massachusetts General Hospital Fertility Center were invited to participate in an ongoing study of environmental factors and fertility. A total of 155 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
5
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 43 publications
5
105
5
2
Order By: Relevance
“…However, an increased intake of antioxidants (antioxidant support) with a higher intake of trans fatty acids may ameliorate the negative effects on sperm quality. 71,79 More clinical trials with sufficient sample sizes are needed to further elucidate the causeand-effect relationship between red or processed meat consumption and male reproductive potential. A positive association of fish intake with sperm concentration and morphology could be mediated through increased intake of long-chain n-3 fatty acids.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, an increased intake of antioxidants (antioxidant support) with a higher intake of trans fatty acids may ameliorate the negative effects on sperm quality. 71,79 More clinical trials with sufficient sample sizes are needed to further elucidate the causeand-effect relationship between red or processed meat consumption and male reproductive potential. A positive association of fish intake with sperm concentration and morphology could be mediated through increased intake of long-chain n-3 fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies that investigated the effect of food intake and dietary habits reported a positive association between higher intake of processed meat and sweets and the risk of low sperm quality (Table 2). 2,25,28,48,63,64,[70][71][72] The remaining studies, which investigated the role of specific micronutrient(s) on indicators of semen quality, reported conflicting results (Table 3). 17,[54][55][56][57][58][59][60][61][62][65][66][67]69 Dietary habits and food intake.…”
Section: Outcomes Of Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…M. Afeiche и соавт. [24] показали, что диета, обогащенная красным и/или обработанным мясом, приводит к нарушению морфологии сперматозои-дов, а потребление рыбы, напротив, сопровождается ростом общего количества гамет и доли морфологи-чески нормальных клеток, особенно при полном за-мещении мяса морепродуктами.…”
unclassified